Resistance Coefficient at the Lower Surface of an Ice Cover - Sokolov,I. N. (1970)
For solution of a number of problems of hydraulic flow and for calculation of the dynamic ice pressure on hydrotechnical structures, it is necessary to know the resistance coefficient at the lower surface of an ice cover. The present article gives data on the value of the resistance coefficient for a flat lower surface of ice, obtained by experiments with small blocks of ice in the shape of rectangular plates. The test consisted of measuring the net force on ice blocks of given dimensions floating on he surface of the water with the current at different rates of flow. The resistance coefficient at the water-ice boundary was calculated from the test results. (Author) Trans. of Meteorologiya i Gidrologiya (USSR) n4 p34-36 Apr 1960.